Molecular interactions between entomopathogenic fungi (Hypocreales) and their insect host: Perspectives from stressful cuticle and hemolymph battlefields and the potential of dual RNA sequencing for future studies - Pedrini, Nicolás (2018)
Entomopathogenic fungi of the order Hypocreales infect their insect hosts mainly by penetrating through the cuticle and colonize them by proliferating throughout the body cavity. In order to ensure a successful infection, fungi first produce a variety of degrading enzymes that help to breach the insect cuticle, and then secrete toxic secondary metabolites that facilitate fungal invasion of the hemolymph. In response, insect hosts activate their innate immune system by triggering both cellular and humoral immune reactions. As fungi are exposed to stress in both cuticle and hemolymph, several mechanisms are activated not only to deal with this situation but also to mimic host epitopes and evade the insect's immune response. In this review, several components involved in the molecular interaction between insects and fungal pathogens are described including chemical, metabolomics, and dual transcriptomics approaches; with emphasis in the involvement of cuticle surface components in (pre-) infection processes, and fungal secondary metabolite (non-ribosomally synthesized peptides and polyketides) analysis. Some of the mechanisms involved in such interaction are also discussed.